Desenvolvimento de novos vetores bem regulados para Escherichia coli - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
In this work, a set of regulated expression vectors was constructed for purposes of cloning and expression of heterologous genes in Escherichia coli. Promoters are essential elements of the expression cassettes used in this type of vectors. The vectors, derived from this work, which express heterologous genes at different levels and in a well-regulated way were based on a synthetic promoter called DM. DM promoter activity can be modulated by both IPTG and glucose. The plasmids named: pDM02 (low copy), pCDM (low copy), pDMU01 (high copy) and pDMU02 (high copy) were capable of expressing at high levels and in a regulated manner in E. coli the gene sequences of GFP (Green Fluorescent Protein), human thioredoxin fused with bovine enterokinase and tambaqui growth hormone. The DM promoter sequence was modified by means of random chemical DNA synthesis to construct a library of new synthetic promoters and these were then ligated into the pCDM vector in an appropriate position to express the GFP reporter gene. E. coli clones containing recombinant plasmids with different promoters were obtained. A group of clones that had new promoter sequences maintained glucose regulation and had higher levels of expression, while another group of clones showed a lower level of glucose regulation, but with much higher levels of GFP expression. The results show that the new synthetic promoters can be used for the development of new, potent and regulated expression vectors for the expression of heterologous genes for both research and bioindustrial purposes.
Keywords: Tambaqui (Peixe) - Crescimento; Hormônios - Regulação; Peixes - Crescimento; CIENCIAS BIOLOGICAS; Promotor sintético regulado; Vetores de expressão; Regulação do operon lac; Hormônio de crescimento de tambaqui